The role of 4PL provider as a mediation and supply chain agility - Macide Berna Çağlar Kalkan; Kenan Aydın (Modern Supply Chain Research and Applications, 2020)
Purpose - The aim of this study is to examine the role and capabilities of fourth party logistics (4PL) in the supply chain agility and firm performance. In addition to this, the relationship between supply chain agility and firm performance is also examined. This study aims to fulfill the gap in the literature about the studies on the relationship between 4PL capability dimensions, supply chain agility and business performance. Design/methodology/approach - The study uses survey data from 58 senior executives and managers in the logistics and supply chain functions from 4PL service providers' customer firms in Turkey. The results are structural equation modeling using SmartPLS software. Snowball sampling method was used to collect survey data. Findings - This study shows that integrator and supply chain infomediary are appropriate practices for mediating the impact of agile supply chain strategies, on firm performance. For supply chain practitioners, results indicate that firms benefit greatly if they consider the outsourcing, such as a 4PL partnership, in conjunction with their supply chain strategy. Research limitations/implications - Time, cost and the presence of businesses located in different cities across Turkey in the sample of study and the existence of the tendency of enterprises not to participate in the research can be stated as the limitations of this study. Originality/value - In the literature, studies on 4PL have been conducted in different fields which can be categorized as follows: 4PL solution development, reasons that facilitate and prevent the design and implementation of 4PL, scope of 4PL service delivery and profit and risk sharing from the structure of 4PL networks. Briefly, the studies focus on conceptualizing and differentiating of 4PL from 3PL before reaching a common definition. Motivation of this study is to fulfill the gap of literature about supply chain agility, firm performance relationship and mediation role of 4PL skill dimensions.
Keywords: 650; Fourth party logistics; Integrator; Supply chain agility; Supply chain infomediary